Efectividad de las intervenciones educativas para la prevención del embarazo en adolescentes. - Chávez Oleas, Katherin Estefanía (2025)
Teenage pregnancy is a highly complex public health problem closely linked to social, cultural, and economic determinants. The main objective of this research was to analyze the effectiveness of educational interventions for the prevention of teenage pregnancy through a documentary literature review. Using a quantitative, descriptive approach, a total of 25 selected studies were evaluated according to methodological quality criteria using the CRF-QS instrument, a tool designed to assess the quality of scientific studies based on criteria of methodological rigor, relevance, and internal validity. The results reveal that well-structured educational interventions have a positive impact on increasing knowledge, changing attitudes, and the adoption of preventive behaviors against early pregnancy. However, their effectiveness is limited by multiple structural barriers such as poverty, domestic violence, poor parental communication, and the persistence of cultural myths surrounding sexuality. A direct correlation was also identified between comprehensive sexuality education and the informed use of contraceptive methods among adolescents. The analysis of the studies demonstrated that the evidence supports the need to strengthen the participation of nursing staff in educational units by implementing intersectoral strategies with a culturally relevant approach. In conclusion, adolescent pregnancy prevention requires a comprehensive and multisectoral approach, where education, psychosocial support, and comprehensive access to contraceptive methods are part of a coordinated intervention system that is sustainable over time and tailored to local conditions.